2021
DOI: 10.1093/nar/gkab935
|View full text |Cite
|
Sign up to set email alerts
|

A balancing act in transcription regulation by response regulators: titration of transcription factor activity by decoy DNA binding sites

Abstract: Studies of transcription regulation are often focused on binding of transcription factors (TFs) to a small number of promoters of interest. It is often assumed that TFs are in great excess to their binding sites (TFBSs) and competition for TFs between DNA sites is seldom considered. With increasing evidence that TFBSs are exceedingly abundant for many TFs and significant variations in TF and TFBS numbers occur during growth, the interplay between a TF and all TFBSs should not be ignored. Here, we use additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…Interestingly, previous studies have suggested that repetitive elements or even transgenes might serve as sinks for TF binding (31)(32)(33)(34)(35)(36). Studies in bacteria have been particularly important in exploring the stoichiometry between TF protein level and TF binding sites and suggest that certain TFs may be more susceptible to titration effects than others (35,36).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, previous studies have suggested that repetitive elements or even transgenes might serve as sinks for TF binding (31)(32)(33)(34)(35)(36). Studies in bacteria have been particularly important in exploring the stoichiometry between TF protein level and TF binding sites and suggest that certain TFs may be more susceptible to titration effects than others (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, previous studies have suggested that repetitive elements or even transgenes might serve as sinks for TF binding (31)(32)(33)(34)(35)(36). Studies in bacteria have been particularly important in exploring the stoichiometry between TF protein level and TF binding sites and suggest that certain TFs may be more susceptible to titration effects than others (35,36). While these studies provide important conceptual advances in our understanding of the biophysical determinants of transcription at the level of transcription factor binding, they use exogenous cellular perturbations and do not always mimic molecular mechanisms relevant to eukaryotic cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Global regulators are known to bind to a collection of sites, and the regulatory effect on each binding site would be dependent on the protein concentration at any given moment, its affinity, and additional transcription factors. Hence, they can be activators, repressors, have dual regulatory roles, or have no described regulatory function [103][104][105][106][107].…”
Section: Plos Onementioning
confidence: 99%
“…Conversely V2 transcription of guide 1 may be less than in V1 due to local competition for transcription factors between the 4 closely linked TaU6/TaU3 promoters in V2. Reduced promoter activity resulting from the addition of decoy transcription factor binding sites has been reported (Gao et al, 2021). Knockout of both copies of HORVU.MOREX.r3.2HG0184740 is expected to result in the conversion of tworowed Golden Promise spikes into six row spikes (Komatsuda et al, 2007).…”
mentioning
confidence: 99%